Virulence of entomopathogenic nematodes (Rhabditida: Steinernematidae, Heterorhabditidae) to spittlebug Mahanarva spectabilis (Hemiptera: Cercopidae) - Batista,Elder Simões de Paula (2014)
The spittlebug can seriously limit the production of forage, and the use of chemical products to control insect pests is costly and can harm the environment. Thus, there is a need to reduce the reliance on chemical agents by developing new strategies. The virulence of nine strains of entomopathogenic nematodes (EPNs) to spittlebugs was investigated under laboratory and greenhouse conditions. Fourth/fifth-instar nymphs of Mahanarva spectabilis were exposed to EPNs in the laboratory and the most virulent strains were applied on the nymphs in the greenhouse at concentrations of 2,000 and 4,000 EPNs/mL. The efficacy of the pathogenic agent was confirmed by the dissection of dead hosts. All the tested strains were pathogenic to the M. spectabilis nymphs in laboratory, particularly Steinernema carpocapsae, S. feltiae, S. riobraveand Heterorhabditis amazonensisRSC1, each of which caused nymph mortality higher than 80%. The concentration did not influence the efficiency of the strains, and those selected in the laboratory had similar efficiency in the greenhouse, except for S. carpocapsae, which was not as effective as the others. Entomopathogenic nematodes can be included in integrated pest management programs to M. spectabilis.